2006 International SiGe Technology and Device Meeting 2006
DOI: 10.1109/istdm.2006.246562
|View full text |Cite
|
Sign up to set email alerts
|

X-band and K-band low-phase-noise VCOs using SiGe BiCMOS technology

Abstract: From the past two decades, SiGe transistors have been identified as excellent candidates to match requirements both for high purity signal generation and high frequency applications. Moreover, SiGe BiCMOS technology takes benefit of CMOS devices that allow high integration levels for Monolithic Microwave Integrated Circuits (MMIC) Phase Locked Loop (PLL) systems. This work focuses on the only analog circuit of a PLL: the Voltage Controlled Oscillator (VCO) is one of the key stone of a transceiver, because its … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(14 citation statements)
references
References 4 publications
0
14
0
Order By: Relevance
“…The second FOM of the proposed VCO is about À171.38 dBc/Hz, it is calculated using the figure of merit defined as [10][11][12] …”
Section: Measurement and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The second FOM of the proposed VCO is about À171.38 dBc/Hz, it is calculated using the figure of merit defined as [10][11][12] …”
Section: Measurement and Discussionmentioning
confidence: 99%
“…It requires a low phase noise, low cost, and high output power. A lot of VCO circuit architectures such as cross-coupled oscillators [2], Colpitts oscillator [3,4] and Hartley oscillator [5] can be used to design a high performance K-band VCO. Despite so many options available, design and optimization of an integrated K-band LC VCO still pose many challenges to circuit designers as simultaneous optimization of multiple variables is required.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, in Equation ( 2), the SSB rejected noise is already normalized by the output power in L ( f m ). These considerations have been used to augment Equation (2) into FoM P RF by formally considering such a signal swing (then dynamic power P out ) in Equation (3) [16], as it decides whether or not a buffer amplifier is needed when connecting the VCO to the mixer.…”
Section: Voltage Controlled Oscillatormentioning
confidence: 99%
“…In addition, since this is evaluating tunable oscillators, Equation (4) adds the tuning range in the previous equations, expressed in percentage through TR% in FoM P RF &T , with a small adjustment from the expression first proposed in [16] and also used in other works, some of them being referenced in the dedicated figure later in this article.…”
Section: Voltage Controlled Oscillatormentioning
confidence: 99%
“…From previous work [10], it has been found that emitter‐base V be (which controls I c ) fluctuations mainly influence the phase noise for bipolar devices. Furthermore, according to the phase‐noise model of Hajimiri and Lee [11], the transistor should be operated in class C under oscillation conditions to reduce significantly the phase noise due to the cyclostationary noise.…”
Section: Oscillator Designmentioning
confidence: 99%